Analysis of typologies of money laundering in fulfillment of export transactions - J. M. Beketnova (Управление)
Despite the high level of state control, the sphere of international trade is attractive to malefactors and can be used to with-draw dirty money abroad, or invest it in the legal economy under the guise of honestly earned income. To successfully solve the problem of laundering the proceeds of crime in the course of foreign economic transactions, a systematic approach and scientific understanding of the empirically obtained results are required. The purpose of the article is to study the current trends in the laundering of proceeds from crime in the conduct of foreign economic activity and methods of counteraction.The paper considers the application of typological analysis in economics and other sciences. The author considers and systematizes typologies of legalization of monetary funds by means of price manipulations – by indicating the underestimated or overstated customs value of goods in the accompanying documentation, as well as by performing pseudo-export operations. The study concludes that the money laundering schemes have typical features, and the typological analysis can increase the effectiveness of the efforts of state bodies in the fight against illegal operations. The article defines the specificity of the analysis of financial monitoring objects, which is due to the high latency of deviant subjects and their activities, the large volume and heterogeneous nature of the information requiring analysis and interpretation, high requirements for professional knowledge and practical experience of expert analysts, as well as significant time costs for the analysis of each individual subject.